2021
DOI: 10.3389/fnmol.2021.797833
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function and Parkinson’s Disease: From the Perspective of the Electron Transport Chain

Abstract: Parkinson’s disease (PD) is known as a mitochondrial disease. Some even regarded it specifically as a disorder of the complex I of the electron transport chain (ETC). The ETC is fundamental for mitochondrial energy production which is essential for neuronal health. In the past two decades, more than 20 PD-associated genes have been identified. Some are directly involved in mitochondrial functions, such as PRKN, PINK1, and DJ-1. While other PD-associate genes, such as LRRK2, SNCA, and GBA1, regulate lysosomal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 189 publications
(213 reference statements)
0
18
0
Order By: Relevance
“…Mitophagy is mediated by these genes via the PINK1/parkin pathway. PINK1 protein is a mitochondrial kinase, parkin is an E3 ubiquitin ligase, and DJ-1 protein participate in proteasome degradation (Panicker et al, 2017;Li et al, 2021).…”
Section: Pten-induced Putative Kinase 1/parkin/dj-1 and Astrocytesmentioning
confidence: 99%
“…Mitophagy is mediated by these genes via the PINK1/parkin pathway. PINK1 protein is a mitochondrial kinase, parkin is an E3 ubiquitin ligase, and DJ-1 protein participate in proteasome degradation (Panicker et al, 2017;Li et al, 2021).…”
Section: Pten-induced Putative Kinase 1/parkin/dj-1 and Astrocytesmentioning
confidence: 99%
“…It has been shown that mitochondrial dysfunction influences the pathology of PD, especially when considering mitochondrial CI [ 39 , 40 ]. CI is the initial electron acceptor of NADH in the ETC, and the disruption of this complex results in a dramatic loss of energetic capacity.…”
Section: Bioenergetics and Neurodegenerationmentioning
confidence: 99%
“…During electron transfer, three of these complexes (complexes I, III, and IV) pump protons from the matrix to the mitochondrial intermembrane space (IMS), thereby generating an electrochemical proton gradient across the IMM that the F 1 F o -ATP Synthase (also known as ATPase Synthase or complex V) exploits to drive ATP synthesis from adenosine diphosphate (ADP; Breuer et al, 2013 ; Guo R. et al, 2018 ; Signes and Fernandez-Vizarra, 2018 ; Nolfi-Donegan et al, 2020 ). The fundamental role of ETC in mitochondrial energy production is essential for neuronal survival and activity (Li et al, 2021a ). However, both complexes I and III can also transfer single electrons to oxygen, resulting in the formation of oxygen superoxide in the mitochondrial matrix.…”
Section: Dysregulation Of Mitochondrial Bioenergeticsmentioning
confidence: 99%